All-Inside Repair of Complex Posterior Horn Meniscus Tears - Sahil Dadoo BS; Bálint Zsidai MD; Laura Keeling MD; Volker Musahl MD (SAGE Publishing, 2023)
Background: Due to difficult-to-access location and complex tear patterns, the management of meniscus injuries in isolation and in conjunction with anterior cruciate ligament injury may be challenging. The aim of this video is to present techniques and tips that may help surgeons perform arthroscopic all-inside repair of complex meniscus tears. Indications: Indications for the presented repair techniques are young patients with high activity demands, symptomatic lateral and medial meniscus lesions, ligamentous knee instability, chondral changes grade 2 or less, neutral joint alignment, and body mass index below 35 kg/m 2 . Technique Description: High anterolateral, low anteromedial, and accessory anterolateral portals are used for the arthroscopic assessment of meniscus tear quality and pattern, and to ensure adequate access to the lesion. Horizontal mattress, vertical mattress, and cerclage sutures are passed using a range of all-inside devices to approximate tear edges with the aim of restoring native hoop stresses along the circumferential meniscus collagen fibers. Tear edges are abraded to enhance healing potential. Two separate cases and complex tear configurations are presented to illustrate these all-inside meniscus repair techniques. Results: Meniscus repair yields superior long-term outcomes compared with partial meniscectomy. Improvements in subjective knee function and lower rates of progression to long-term knee osteoarthritis are reported in patients treated with meniscus repair versus resection. Advantages of all-inside meniscus repair include the reduced risk of iatrogenic neurovascular lesions, decreased operative time, restoration of native contact surfaces, and repair without fixation of the menisci to the surrounding soft tissue. Discussion/Conclusion: Arthroscopic all-inside meniscus repair enables the safe and efficient management of complex meniscus tears in active patients with symptomatic meniscus pathology, and can be performed concurrent with knee ligament surgery. Consequently, all-inside meniscus repair techniques are a versatile addition to the toolkit of complex knee surgeons. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.